Successful Treatment of Alopecia Areata Patches with Triamcinolone Acetonide Using MMP®: Report of 2 Cases - Barletta, Marina (Skin Appendage Disord, 2020)
Intralesional (IL) injection of corticosteroids is an effective treatment of alopecia areata (AA). A novel drug delivery technique that uses a tattoo machine (MMP®) has been successfully used to treat other skin disorders. We tested this technique to treat AA. We used the Cheyenne dermopigmentation machine (Anvisa 80281110016; Germany) with a 27 Magnum needle cartridge (Anvisa 80281110015) at a frequency of 70 Hz and needle depth of 1.0 mm. A triamcinolone acetonide (TAC) solution was placed in a sterile receptacle and loaded onto the cartridge by capillarity. We produced micropunctures of the skin with the medication-soaked needles until the affected area was covered by a bloody dew. Case 1: J.C.V., a male, with a diagnosis of AA in patches was treated with 1-monthly session with 2.5 mg/mL TAC delivered by MMP® (4 sessions in total). Case 2: L.M.V., a 78-year-old female with a diagnosis of AA was treated with 1-monthly session with 10 mg/mL TAC delivered by MMP® (4 sessions in total). MMP® is a novel technique that combines microneedling with drug delivery, and it could be used to deliver IL TAC to AA patients. This technique promotes a more uniform absorption of corticosteroids than traditional treatment methods of AA.